Diagnosis of Mineral Deficiencies in Teak (Tectona grandis) Seedlings - Kaul, O. N.; Gupta, A. C.; Negi, J. D. S. (Indian Forester, 1972)
The paper describes the morphological symptoms caused by the deficiency of some macronutrients ou teak (Tectona grandis) seedlings and their effect on growth, dry matter production and nutrient uptake. The results indicate that recognisable deficiency symptoms were caused by the absence of each of the macronutrients. Unlike some other forest species studied so far, deficiency of sulphur caused distinct symptoms of chlorosis, curling of leaves and premature defoliation with restricted shoot growth. The deficiency of all the elements except that of potassium significantly reduced height growth and dry matter production.